The tourism attractiveness of Polish libraries - Miedzińska, Magdalena; Tanaś, Sławoj (Turyzm/Tourism, 2009)
The aim of the article is to draw the reader's attention to the tourism attractiveness of renowned Polish libraries. These have attained a tourism function due to tourism exploration and penetration, but remain in the shadow of other Polish cultural assets. The article outlines the historical geography of Polish libraries, an analysis of tourism assets and an attempt to classify and catalogue libraries in Poland.